Novel Application of 3D Scaffolds of Poly(E-Caprolactone)/Graphene as Osteoinductive Properties in Bone Defect - Budi, Hendrik Setia; Anitasari, Silvia; Shen, Yung-Kang; Tangwattanachuleeporn, Marut; Nuraini, Prawati; Setiabudi, Narendra Arya (European Journal of Dentistry, 2022)
Objective Scaffolds provided a surface on which cells could attach, proliferate, and differentiate. Nowadays, bone tissue engineering offers hope for treating bone cancer. Poly(e-caprolactone) (PCL)/graphene have capability as an osteogenic and regenerative therapy. It could be used to produce bone tissue engineering scaffolds. The purpose of this study was to investigate the ability of PCL/graphene to enhance the osteoinductive mechanism.Materials and Methods The PCL/graphene scaffold was developed utilizing a particulate-leaching process and cultured with osteoblast-like cells MG63 at 0.5, 1.5, and 2.5 wt% of graphene. We evaluated the porosity, pore size, migratory cells, and cell attachment of the scaffold.Statistical Analysis Data was expressed as the mean ± standard error of the mean and statistical analyses were performed using one-way analysis of variance and Tukey's post hoc at a level of p-value < 0.05.Results Porosity of scaffold with various percentage of graphene was nonsignificant (p > 0.05). There were differences in the acceleration of cell migration following wound closure between groups at 24 hours (p < 0.01) and 48 hours (p < 0.00). Adding the graphene on the scaffolds enhanced migration of osteoblast cells culture and possibility to attach. Graphene on 2.5 wt% exhibited good characteristics over other concentrations.Conclusion This finding suggests that PCL/graphene composites may have potential applications in bone tissue engineering.
Keywords: PCL; graphene; scaffold; osteoinductive; tissue engineering